1984
DOI: 10.1055/s-2007-1014863
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Absorption of U-40 and U-100 Insulin

Abstract: Single strength insulin has been recommended in order to reduce dosage errors (Bloom, Keen and Watkins 1981). Most of Europe uses insulin of 40 units/ml (U-40) only, whereas the United States, Canada, Australia, and, recently, Britain have adopted a sole insulin strength of 100 units/ml (U-100). We studied the absorption of identical doses of soluble U-40 and U-100 insulin after a) subcutaneous injection, b) during continuous subcutaneous insulin infusion (SCII), and c) a supplementary meal bolus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…A range of studies have described concentration‐dependent absorption kinetics of subcutaneous bolus injection of human insulin . The different studies concerning human insulin, in different concentrations, showed varying outcomes . Several studies displayed a difference between U40 and U100 human insulin while others failed to do so .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A range of studies have described concentration‐dependent absorption kinetics of subcutaneous bolus injection of human insulin . The different studies concerning human insulin, in different concentrations, showed varying outcomes . Several studies displayed a difference between U40 and U100 human insulin while others failed to do so .…”
Section: Discussionmentioning
confidence: 99%
“…The different studies concerning human insulin, in different concentrations, showed varying outcomes . Several studies displayed a difference between U40 and U100 human insulin while others failed to do so . One of them showed a small but significant difference after 1.5 h, and another showed an initial difference, whereas two studies showed significance at 30 and 45 min after injection .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…between 10 and 5000 IU/ml [5] slower absorption of more concentrated insulin was most clearly demonstrated. Reports concerning differences in pharmacokinetic properties between 40 IU/ml insulin (U40) and 100 IU/ml (U100) have been inconsistent, mainly due to small sample sizes [6][7][8]. The following study assesses the impact of a 2.5-fold increase from U40-to U100-insulin on insulin absorption from the subcutaneous depot, as well as confounding anthropometric variables in a large sample of healthy subjects.…”
mentioning
confidence: 99%